Recent Studies on Cancer Cell’s Inhibition by Organotin (IV) Materials: An Overview - Ibadi, Falih; Yousif, Emad; Al-Mashhadani, Mohammed; Hairunisa, Nany; Bufaroosha, Muna (Al-Nahrain Journal of Science, 2023)
Organotin (IV) compounds have been the focus of recent studies for their potential use in the treatment of cancer. This review provides an overview of recent studies on the inhibition of cancer cells by organotin (IV) materials. The literature suggests that organotin (IV) compounds can selectively target cancer cells and induce apoptosis, making them promising candidates for anticancer drugs. The review covers various types of organotin (IV) compounds, including those containing alkyl, aryl, and amino groups, and their mechanisms of action against cancer cells. Additionally, the study explores the potential toxicity and biocompatibility of these compounds and their derivatives, as well as their potential use in combination therapy. Overall, the results of recent studies suggest that organotin (IV) compounds show great potential for the treatment of cancer. However, more research is needed to fully understand their mechanism of action and potential side effects. The review highlights the need for continued investigation of these compounds and their derivatives to develop effective and safe anticancer therapies.